Arthropod diversity patterns in three coastal marshes in Terceira Island (Azores) - Borges, Paulo A. V. (2017)
The coastal wet areas of Praia da Vitória (Terceira, Azores) were investigated to describe the ground and aerial (herbaceous and canopy) arthropod communities by comparing patterns of species composition, abundance and diversity. Three wet areas were studied: Paul da Praia da Vitória (PPV), Paul do Belo Jardim (PBJ) and Paul da Pedreira do Cabo da Praia (PPCP). A standardized protocol (based on the COBRA protocol) was performed with day and night sampling of arthropods with a total of 56 samples per site. Common diversity metrics (Hill series) were calculated and abundance patterns were investigated using species abundance distributions (SAD). All investigated communities were dominated by native non-endemic and exotic species; only seven out of the 132 endemic arthropod species and subspecies existing in Terceira Island were found in the area. The logseries described well the communities, with a prevalence of rare species. The three sites seem to work as a complementary network of wet areas with specific arthropod communities possibly related to their specific features. However, Paul do Belo Jardim (PBJ) performed better for many of the investigated indicators, and two IUCN endangered species, the true weevil Drouetius oceanicus oceanicus and the Azorean cone-head grasshopper (Conocephalus chavesi) are relatively abundant there. Due to habitat changes that occurred between 2006 and 2010 in PPV, only one of the three most abundant ground-beetles recorded in 1991-1993 and 2003 was found but only after some additional sampling in a small remnant of the original habitat.